2005
DOI: 10.4049/jimmunol.175.8.5104
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role for the Tapasin-Docking Site of TAP2 in the Functional Integrity of the MHC Class I-Peptide-Loading Complex

Abstract: The transporter associated with Ag processing (TAP) translocates antigenic peptides into the endoplasmic reticulum for binding onto MHC class I (MHC I) molecules. Tapasin organizes a peptide-loading complex (PLC) by recruiting MHC I and accessory chaperones to the N-terminal regions (N domains) of the TAP subunits TAP1 and TAP2. To investigate the function of the tapasin-docking sites of TAP in MHC I processing, we expressed N-terminally truncated variants of TAP1 and TAP2 in combination with wild-type chains,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
104
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 56 publications
(116 citation statements)
references
References 43 publications
12
104
0
Order By: Relevance
“…TAP2 is predicted to span the membrane nine times, with the N terminus of the membrane domain in the ER lumen and the C terminus in the cytosol (14, 39). The C-terminal six transmembrane domains of TAP1 and TAP2 combine to form the core unit of the transporter that is responsible for peptide binding and translocation, whereas the N-terminal transmembrane domains of TAP1 and TAP2 interact with tapasin (21,22,28,36).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…TAP2 is predicted to span the membrane nine times, with the N terminus of the membrane domain in the ER lumen and the C terminus in the cytosol (14, 39). The C-terminal six transmembrane domains of TAP1 and TAP2 combine to form the core unit of the transporter that is responsible for peptide binding and translocation, whereas the N-terminal transmembrane domains of TAP1 and TAP2 interact with tapasin (21,22,28,36).…”
mentioning
confidence: 99%
“…TAP2 is predicted to span the membrane nine times, with the N terminus of the membrane domain in the ER lumen and the C terminus in the cytosol (14, 39). The C-terminal six transmembrane domains of TAP1 and TAP2 combine to form the core unit of the transporter that is responsible for peptide binding and translocation, whereas the N-terminal transmembrane domains of TAP1 and TAP2 interact with tapasin (21,22,28,36).Since the vast majority of peptides presented to CTLs require translocation into the ER by TAP, it is not surprisingly that many viruses interfere with this transport step (3, 8, 12, 17, 18, 23-25, 30, 35, 37, 41). Human cytomegalovirus (HCMV) encodes the protein US6, which is an ER-localized type I integral membrane glycoprotein that inhibits peptide translocation by TAP (2,15,27).…”
mentioning
confidence: 99%
“…It has been shown that both TAP1 and TAP2 subunits possess binding sites for tpn at their N-terminal TMSs [10][11][12]. The exact stoichiometry of the PLC has been a matter of debate [13,14]; however, recent findings demonstrate a TAP-tpn ratio of 1:2 [15,16] as proposed previously also by Rufer et al [17].…”
Section: Introductionmentioning
confidence: 49%
“…Since our HLA-B*44:02 stability analysis never showed a complete loss in the presence of TPSN Ex3, the data indicate, that more than one active MHC-I loading site per TAP molecule exist, which has recently been proposed also by others [15,16]. Furthermore, since TPSN Ex3 was not able to displace tpn completely from the TAP complex, it suggests, in a functional sense, that there are at least two differing binding sites for tpn on TAP, which has been observed previously for rat TAP subunits [11]. Since TPSN Ex3 appears to bind to a subset of these binding sites, in future studies TPSN Ex3 might be instrumental to gain further insights into the functional stoichiometry of the PLC.…”
mentioning
confidence: 48%
See 1 more Smart Citation